2022
DOI: 10.3390/biology11010112
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa and Drought Stress in Olive Trees: A Complex Relationship Mediated by Soluble Sugars

Abstract: Xylella fastidiosa (Xf) subsp. pauca “De Donno” is the etiological agent of “Olive Quick Decline Syndrome” (OQDS) on olive trees (Olea europaea L.); the presence of the bacterium causes xylem vessel occlusions inducing a drought stress and the development of leaf scorch symptoms, which may be worsened by water shortage in summer. In order to evaluate how the two stress factors overlap each other, the carbohydrate content and the expression patterns of genes related to carbohydrate metabolism have been evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 96 publications
(102 reference statements)
2
15
0
Order By: Relevance
“…Considering that all infected plants, regardless of the cultivar, had similar Cq-values (i.e., similar bacterial load), the variations of the physiological parameters detected in our study are more likely the consequence of the differential host response to the bacterial infections rather than the direct influence of the pathogen abundance. The present data supports molecular evidences and extensive field surveys concluding that there is a different susceptibility of olive cultivars to X. fastidiosa infection (Habermann et al, 2003b ; Boscia et al, 2017b ; De Pascali et al, 2022 ). Indeed, this study is a preliminary step to introduce a phenomics approach in the screening of susceptible/resistant genotypes to X. fastidiosa .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering that all infected plants, regardless of the cultivar, had similar Cq-values (i.e., similar bacterial load), the variations of the physiological parameters detected in our study are more likely the consequence of the differential host response to the bacterial infections rather than the direct influence of the pathogen abundance. The present data supports molecular evidences and extensive field surveys concluding that there is a different susceptibility of olive cultivars to X. fastidiosa infection (Habermann et al, 2003b ; Boscia et al, 2017b ; De Pascali et al, 2022 ). Indeed, this study is a preliminary step to introduce a phenomics approach in the screening of susceptible/resistant genotypes to X. fastidiosa .…”
Section: Discussionsupporting
confidence: 89%
“…Although the mechanisms of resistance in Leccino and FS17 trees are still unclear, in a recent study, Leccino was found to be constitutively less susceptible to xylem cavitation than Cellina di Nardò, and was able to activate more efficient refilling mechanisms, thus rapidly restoring vessel's hydraulic conductivity (Sabella et al, 2019 ). Moreover, it has been hypothesized that the resistance of Leccino to Xfp could be related to its response to water stress, which could elicit defense pathways against Xfp mediated by sugars (De Pascali et al, 2022 ). In addition, molecular mechanisms entailing the plant cell wall receptors have been described in transcriptome studies (Giampetruzzi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pauca subspecies causes nerve chlorosis in citrus and develops on fewer hosts. In Italy, it was found in coffee as well as olive plants (EFSA Panel on Plant Health et al, 2018;Luvisi et al, 2017;Mang et al, 2016;Marcelletti and Scortichini, 2016b), representing the first confirmed record of this bacterium in Europe (De Pascali et al, 2022). This subspecies was introduced from Central America where it is an endemic pathogen .…”
Section: Fastidiosa Subspecies Present In Europementioning
confidence: 99%
“…In Italy, X. fastidiosa was first discovered in 2013, in one of the main olive ( Olea europaea L.) production areas—the Salento peninsula in the Apulia region—where it caused OQDS, resulting in the widespread drying of olive trees in this area ( Fig. 1 ), and thus causing enormous socioeconomic and ecological damage ( De Pascali et al, 2022 ; Girelli et al, 2022 ; Martelli et al, 2016 ; Saponari et al, 2013 , 2019 ; Strona et al, 2017 ). The extent of the damage was exacerbated by water scarcity ( De Pascali et al, 2022 ).…”
Section: Geographical Distribution In Europementioning
confidence: 99%
“…Sucrose can be involved in both ROS production pathways, such as regulation of mitochondrial respiration or photosynthesis, and NADPH production pathways, such as the oxidized pentose phosphate pathway, when plants are exposed to stress [11,12]. Sucrose accumulation is associated with increased plant tolerance to abiotic stresses, and De Pascali et al [13] studied olive trees under dual pathogen and drought stress in which they found a remarkable decline in sucrose content in susceptible varieties and a signi cant increase in resistant varieties, as well as found that in resistant varieties, the combination of drought and pathogen stress increased the expression of all genes involved in sugar metabolism and transport.…”
Section: Introductionmentioning
confidence: 99%